Guidelines for Clinicians and Pathologists on Performing Skin Biopsies and Reporting on Suspected Cutaneous Squamous Cell Carcinoma. - Chergui, May; Redpath, Margaret; Wang, Chang Shu; Mlynarek, Alex; Esfahani, Khashayar; Thibaudeau, Stephanie; Sultanem, Khalil; Claveau, Joël (Current Oncology, 2025)
Simple Summary: A common type of skin cancer, called squamous cell carcinoma, is becoming more widespread, and for patients with more serious forms, it can be life-threatening. The way skin samples are currently taken, the information is sent to the lab, and how lab reports are written often differ, making it difficult to get accurate diagnoses and the most effective treatment. To address this, a group of Canadian medical experts has developed clear guidelines. They recommend better methods for doctors to take skin biopsies, more complete information to include on lab request forms, and standardized lab reports that highlight crucial risk factors. Following these recommendations will lead to more precise diagnoses and help medical teams make quicker, more appropriate treatment decisions, ultimately improving patient health and reducing the chances of serious complications from this skin cancer. Cutaneous squamous cell carcinoma (CSCC) is the second most common skin cancer after basal cell carcinoma. When squamous cell carcinomas in situ are included, nonmelanoma skin cancer incidence is nearly equal between CSCC and basal cell carcinoma. The incidence of CSCC has been increasing worldwide in recent decades, and despite the effectiveness of office-based therapies, patients with high-risk lesions associated with advanced CSCC face high rates of recurrence and mortality. This underscores the importance of accurate diagnoses and clear criteria to define high-risk lesions for prognosis and better treatment strategies. However, variability exists in CSCC registration practices internationally, and differences in pathology reporting likely contribute to an underestimate of the true burden of disease. Thus, there is a need to refine elements included in skin biopsy reports to provide a precise representation of the high-risk features of CSCC to improve patient care. In this review, a multidisciplinary group of Canadian experts discuss clinical considerations and provide key guidance and practical strategies surrounding skin biopsy techniques, completion of requisition forms, and dermatopathology reports for CSCC. This article summarizes the expert panel's recommendations with the goal of improving diagnosis and pathological reporting of biopsy specimens to achieve better patient outcomes for CSCC.